2016
DOI: 10.1371/journal.pone.0159744
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Characteristics of Neonatal Extended-Spectrum β-Lactamase-Producing Gram-Negative Bacteremia: A 12-Year Case-Control-Control Study of a Referral Center in Taiwan

Abstract: Extended-spectrum β-lactamase (ESBL)-producing Gram-negative bacteremia (GNB) in the neonatal intensive care unit was characterized by comparison with two control groups: a susceptible control group and a general base population group over 2001 to 2012. The influence of ESBL production on mortality was studied in all study subjects and ESBL-GNB isolates were microbiologically characterized. We identified 77 episodes of ESBL-GNB (14.2% of all neonatal late-onset GNB), which were caused by Klebsiella spp. (62.3%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 43 publications
2
20
2
2
Order By: Relevance
“…Nine studies (Alexiou et al, 2012;Fang et al, 2016;Katsaragakis et al, 2008;Michalopoulos et al, 2011;Tsai et al, 2016;Vasudevan et al, 2014;Vasudevan et al, 2015;Venkatachalam et al, 2014;Young et al, 2007) reported data on history of operative procedures in relation to MDR-GNB infection in this metaanalysis ( Figure 3). No substantial heterogeneity (I 2 = 0%, P>0.10) was observed.…”
Section: Operative Proceduresmentioning
confidence: 89%
See 3 more Smart Citations
“…Nine studies (Alexiou et al, 2012;Fang et al, 2016;Katsaragakis et al, 2008;Michalopoulos et al, 2011;Tsai et al, 2016;Vasudevan et al, 2014;Vasudevan et al, 2015;Venkatachalam et al, 2014;Young et al, 2007) reported data on history of operative procedures in relation to MDR-GNB infection in this metaanalysis ( Figure 3). No substantial heterogeneity (I 2 = 0%, P>0.10) was observed.…”
Section: Operative Proceduresmentioning
confidence: 89%
“…Seventeen studies (Alexiou et al, 2012;Costa, Atta, & Silva, 2015;Fang, Chen, & Zhou, 2016;Katsaragakis et al, 2008;Liu et al, 2015;Lye et al, 2012;Marcos et al, 2011;Michalopoulos et al, 2011;Osthoff, Mcguinness, Wagen, & Eisen, 2015;Patel et al, 2014; Prata-Rocha, Gontijo-Filho, & Melo, 2012;Tsai et al, 2016;Vasudevan, Memon, Mukhopadhyay, Li, & Tambyah, 2015;Vasudevan, Mukhopadhyay, Li, Yuen, & Tambyah, 2014;Venkatachalam et al, 2014;Young, Sabel, & Price, 2007;Zhong et al, 2012) reported the correlation of gender and MDR-GNB infection ( Figure 2). The random effect model was used to pool results (I 2 = 75.4%, P < 0.001).…”
Section: Male Gendermentioning
confidence: 99%
See 2 more Smart Citations
“…The SHV-type ESBLs were the most prevalent among these patients (67% of ESBLs), with most strains being genetically unrelated. In this study, neonates infected with ESBL-GN strains had higher rates of infectious complications (p = 0.008) and adverse outcomes (p=0.049) compared to non-ESBLs [18].…”
Section: Global Epidemiology and Clinical Impact Of Amr In Neonatesmentioning
confidence: 58%